2017
DOI: 10.1002/ajh.24896
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intestinal microbiota and their effects on allogeneic stem cell transplantation

Abstract: The human intestinal microbiota is essential for microbial homeostasis, regulation of metabolism, and intestinal immune tolerance. Rapidly evolving understanding of the importance of the microbiota implicates changes in the composition and function of intestinal microbial communities in an assortment of systemic conditions. Complications following allogeneic stem cell transplant now join the ever-expanding list of pathologic states regulated by intestinal microbiota. Dysbiosis, or disruption of the normal ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 72 publications
2
26
0
3
Order By: Relevance
“…The gut microbiota is associated with the development of aGVHD, and loss of microbiota diversity is an independent risk factor for aGVHD . In this study, we demonstrated that the constitution of the microbiota at engraftment following myeloablative allo‐HSCT is associated with aGVHD.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The gut microbiota is associated with the development of aGVHD, and loss of microbiota diversity is an independent risk factor for aGVHD . In this study, we demonstrated that the constitution of the microbiota at engraftment following myeloablative allo‐HSCT is associated with aGVHD.…”
Section: Discussionmentioning
confidence: 54%
“…The gut microbiota is associated with the development of aGVHD, and loss of microbiota diversity is an independent risk factor for aGVHD. 15,[21][22][23] In this study, we demonstrated that the constitution of the microbiota at engraftment following myeloablative allo-HSCT is associated with aGVHD. Furthermore, we used the LASSO algorithm to develop and validate a model in which the GMS could predict the subsequent occurrence and development of aGVHD.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Several studies have demonstrated a protective effect of enteral feeding in GvHD [32]. On the other hand, total parenteral feeding enhances proinflammatory cytokines [33] and most likely aggravates the immune responses in allo-HSCT patients.…”
Section: Modulators Of the Gut Microbiotamentioning
confidence: 99%